Some Reflections on the Ethical-legal Parallel in Kant’s Religion - Quiroga, Noelia Eva (2021)
The aim of this paper is to contribute to understanding the ethical-legal parallel drawn in Religion within the Boundaries of Mere Reason. I will analyze the similarities, differences and the analogy among the ethical state of nature, the exeundum and the community, on the one side, and the juridical state of nature, the exeundum and the community, on the other. I will argue that moral progress, understood as overcoming radical evil, requires a complement between the ethical and legal-political spheres, given that each area provides a different approach and a different community solution within the same public sphere.